2018
DOI: 10.1016/j.hrthm.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Updated performance of the Micra transcatheter pacemaker in the real-world setting: A comparison to the investigational study and a transvenous historical control

Abstract: Micra Transcatheter Pacing System Post-Approval Registry ClinicalTrials.gov identifier: NCT02536118; Micra Transcatheter Pacing Study ClinicalTrials.gov identifier: NCT02004873.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
275
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 281 publications
(309 citation statements)
references
References 12 publications
24
275
0
10
Order By: Relevance
“…Six major complications occurred in four patients that were related to the Micra procedure or system (Table ). These complications have been reported previously …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Six major complications occurred in four patients that were related to the Micra procedure or system (Table ). These complications have been reported previously …”
Section: Resultssupporting
confidence: 69%
“…The design and rationale for of the Micra PAR study (ClinicalTrials.gov identifier: NCT02536118) have been reported previously . Briefly, the aim of the Micra PAR is to further evaluate short‐ and long‐term safety and performance of the Micra transcatheter pacing system (TPS) when used in the “real‐world” setting following commercial release.…”
Section: Methodsmentioning
confidence: 99%
“…So far, there is a single published case report of a Micra transcatheter pacemaker infection in a patient with prior urinary tract infection and multiple hospitalizations. However, recent prospective studies of this novel leadless pacing technology resulted in the observation of no device‐involved infections despite 2,521 implanted devices followed for 12 months or more 8,10 . This study provides evidence that the coating material for the Micra transcatheter pacemaker, parylene, is more resistant to adhesion by common pathogens that cause pacemaker infections compared to titanium or polyurethane.…”
Section: Discussionmentioning
confidence: 76%
“…Leadless pacemakers eliminate the need for a subcutaneous pocket and associated generator pocket infections. Interestingly, no cases of hematogenous device infections were seen either in any of the leadless pacemaker clinical trials 7–10 . Recently, a provocative clinical observation derived from the Micra transcatheter pacemaker IDE trial showed the absence of device infection in the setting of documented bacteremia or endocarditis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in battery technology and advanced electrical circuitry brought about leadless pacemakers, miniaturized self-contained intracardiac single-chamber pacemakers delivered in the right ventricle through a percutaneous transfemoral catheter based approach [9, 10]. Two systems have been clinically available now for several years and showed clinical efficacy and safety [913]. However, existing leadless pacing systems and the S‑ICD are only available for patients requiring single-chamber right ventricular (RV) pacing or shock-only defibrillation therapy, respectively.…”
Section: Introductionmentioning
confidence: 99%